“Vi søker deg med relevant høyere utdanning”: Kompetansebehov i det bibliotekfaglige profesjonsfeltet - Gjestrum, Liv; Tallerås, Kim; Tveit, Åse Kristine (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2018)
It is claimed that today’s professions are challenged and that they may disappear, either because more tasks are automated, or somewhat less dramatically - because the professions have to redefine their roles, due to technological changes and other reasons. Such changes also challenges institutions that educate professional practitioners. As academic staff, teaching students in library and information science, we need to know what competencies are requested in our professional fields. We have collected and examined job advertisements from the most important national channels, from 2015-18, where workplace is a library institution, or where librarian expertise is specifically mentioned. We have analyzed competencies and educational backgrounds, and we have made comparisons to similar data from 2002.The theoretical perspective of the study is derived from the sociology of professions, and the material has been studied using statistical analysis in combination with qualitative content analysis. The study shows that the fields of practice are looking for significantly different professional skills, depending on the type of institution and position in question. Relevant ICT skills and skills in communication are emphasized in almost all advertisements. The analysis also reveals that today more often than in 2002, candidates with a degree other than in library and information science are targeted for positions in libraries.